Tingkat Kepatuhan Pasien TB Paru Terhadap Penatalaksanaan Program OAT (Obat Anti TB) di Poliklinik Paru RSUD. Sanjiwani Gianyar - Dewi, Ni Kadek Ayu Patni; Pendet, Ni Made Diah Pusparini; Sukarja, I Made; Krisnayani, Ni Made Wina (Akademi Keperawatan Kesdam IX/Udayana, 2018)
ABSTRACT Introduction :Tubercolosis (TB) diseases  is one of the most public health problems in Indonesia. Indonesia known as a the  third highest of TB cases in the world after India and China. In 2010, the Ministry of Health In Indonesia reported that patient with TB in worldwide about 5,8 % cases was found in Indonesia. In Indonesia, TB drugs treatments called the OAT Program. The study about the interpersonal factors who can be related to the compliance of patient with TB determined how important  the role of doctors and other health professionals to do verbal and non verbal communication with patients. The aim of this study was to describe complianced of patient with TB  in OAT program at Sanjiwani general hospital, Gianyar. Method : This was observational descriptive study. Data were collected through questionnaires. The total of patient with TB who participated in this research were 78 collected by consecutive sampling technique. Result :Based on the research, the complianced of patient with TB in OAT program showed that 38 respondent (48,71%) had complianced with the OAT program and 40 respondent (51,28 %) didn’t have compliance with the OAT program. Conclusion :Most of the patient with TB in Sanjiwani general hospital didn’t have compliance with OAT program. ABSTRAK Latar Belakang : Tuberkulosis merupakan salah satu masalah kesehatan penting di Indonesia. Selain itu, Indonesia menduduki peringkat ke-3 negara dengan jumlah penderita TB terbanyak di dunia setelah India dan China. Jumlah penderita TB di Indonesia adalah sekitar 5,8 % pada tahun 2010 dari total jumlah penderita TB dunia. Pengobatan pasien TB dilakukan dengan program OAT. Riset tentang faktor-faktor interpersonal yang mempengaruhi kepatuhan terhadap pengobatan menunjukkan pentingnya sensitifitas dokter dan tenaga kesehatan terhadap komunikasi verbal dan nonverbal pasien. Tujuan penelitian ini untuk menggambarkan kepatuhan pasien TB paru dalam melaksanakan program OAT di Poliklinik Paru RSUD Sanjiwani Gianyar. Metode : Jenis penelitian ini adalah observasional deskriptif. Dengan instrument yang duganakan adalah kuesioner. Pengambilan sample menggunakan teknik sampling yaitu consecutive sampling dengan jumlah sampel sebanyak 78 orang. Hasil : Pada penelitian ini hasil dari tingkat kepatuhan pasien sebanyak 38 responden (48,71 %) yang patuh dan yang tidak patuh sebanyak 40 responden (51,28%). Simpulan : Pasien TB di Poliklinik Paru RSUD Sanjiwani Gianyar lebih banyak tidak patuh terhadap penatalaksanaan program OAT.